2017
DOI: 10.3389/fmicb.2017.01268
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Nitrogen-Fixing and Plant Growth Promoting Pseudomonas Species Isolated from Sugarcane Rhizosphere

Abstract: The study was designed to isolate and characterize Pseudomonas spp. from sugarcane rhizosphere, and to evaluate their plant- growth- promoting (PGP) traits and nitrogenase activity. A biological nitrogen-fixing microbe has great potential to replace chemical fertilizers and be used as a targeted biofertilizer in a plant. A total of 100 isolates from sugarcane rhizosphere, belonging to different species, were isolated; from these, 30 isolates were selected on the basis of preliminary screening, for in vitro ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 91 publications
10
122
0
2
Order By: Relevance
“…However, it is generally accepted that the process of offering is very possible. For example, a non-immobilized nitrogen can not promote the growth of its plant host (sugarcane) compared to wild type (Li et al, 2017). Sugarcane is a nutrient-demanding, fast-growing, C4 photosynthetic plant.…”
Section: The Ability Of Endophytic Bacteria On Nitrogen Fixationmentioning
confidence: 99%
“…However, it is generally accepted that the process of offering is very possible. For example, a non-immobilized nitrogen can not promote the growth of its plant host (sugarcane) compared to wild type (Li et al, 2017). Sugarcane is a nutrient-demanding, fast-growing, C4 photosynthetic plant.…”
Section: The Ability Of Endophytic Bacteria On Nitrogen Fixationmentioning
confidence: 99%
“…It is well known fact that even Proteobacteria members like Pseudomonas can fix atmospheric nitrogen (Yongliang et al 2008). Many authors have also proven that P. putida strains can fix nitrogen under natural and induced conditions (Yongliang et al 2008;Ran et al 1987;Chan et al 1944;Setten et al 2013;Li et al 2017). In the present study the isolate showed 99% homology to P. putida H8234.…”
Section: Results and Discussion Morphological And Biochemical Charactmentioning
confidence: 99%
“…The 16S rDNA gene sequence obtained from the isolated bacteria was subjected to phylogenetic analysis using MEGA X. The evolutionary history was inferred using the Neighbor-Joining method (Li et al 2017).…”
Section: Molecular Phylogenetic Analysismentioning
confidence: 99%
“…The strains CY4 (P. koreensis) and CN11 (P. entomophila) show nifH gene expression in sugarcane (the nifH gene has to do with nitrogen fixation). Inoculation of the strains may be an imminent development for biofertiliser application, for sustainable crop production, in reducing environmental pollution, and in biological agri-business [11]. The inoculation of red beets with the nitrogen-fixing bacteria Pseudomonas putida 23 increased the activity of nitrogen fixation in the rhizosphere of plants grown in meadow soil in the central part of the Oka River floodplain [12].…”
Section: Identification and Phylogenetic Analysis Of Selected Strainsmentioning
confidence: 99%